Synergistic Effects of Steel Fibers and Silica Fume on Concrete Exposed to High Temperatures and Gamma Radiation - Mahmut Durmaz (Buildings)
The study explores the resistance of high-strength C40/50 concrete with steel fiber and silica fume admixture to high temperature and gamma radiation. The purpose is to create concrete composites with radiation shielding properties and high temperature resistance for use in nuclear power plants and radioactive waste storage facilities. For that purpose, concrete specimens containing 0.64 wt% industrial steel fiber and different proportions of silica fume (0%, 5%, 10%, 15%) were first subjected to high temperature according to ISO 834 and ASTM E119 after 28 days of curing at a target temperature of 900 °C based on a working fire scenario and then subjected to 94 kGy gamma radiation and analyzed using compressive strength, flexural strength, ultrasonic pulse velocity (UPV), SEM-EDX and XRD tests. It was found that 94 kGy gamma radiation increased the compressive strength of steel fiber concrete by SFC 20.98%, SFC-5 26.36%, SFC-10 26.45%, and SFC-15 25.34%, flexural strength by SFC 24.85%, SFC-5 25.06%, SFC-10 24.11%, and SFC-15 23.65%, and led to microstructure improvement and densification. XRD analysis revealed that samples exposed to 94 kGy gamma radiation accumulated and increased their calcite peak, resulting in decreased porosity and increased compressive and flexural strength. Under high temperature (900 °C) conditions, a significant decrease in the mechanical properties of concrete was observed in the compressive strength of SFC 78.99%, SFC-5 76.71%, SFC-10 76.62% and SFC-15 76.05% and in the flexural strength of SFC 79.44%, SFC-5 78.66%, SFC-10 79.68% and SFC-15 80.11%. In conclusion, results highlight the synergistic role of silica fume in reducing porosity and enhancing radiation-induced cement matrix reactivity, as well as that of steel fibers in improving thermal shock resistance and residual mechanical integrity. The developed composite materials are promising candidates for structural and shielding components in nuclear reactors, radioactive waste storage units, and other critical infrastructures requiring long-term durability under combined thermal and radiological loading.